Modulatory Effects of Dexamethasone upon Virulence Attributes of Pseudomonas Aeruginosa ATCC® 27853™. Issue 1 (2015) - Ferreira, L.E.; Gregio, A.M.T.; Alanis, L.R.A.; Trevilatto, P.C.; Campelo, P.M.; Groppo, F.C.; Rosa, E.A.R.
No abstract available